Study of the response to the glycemic index of rice starch (Oryza sativa L) modified by physical and enzymatic treatment - Lailatul Azkiyah; Yuli Witono; Noven Kristina Br. Silalahi; Ardiyan Dwi Masahid; Fifteen Aprilia Fajrin; Hadi Paramu; Didik Pudji Restanto (AcTion: Aceh Nutrition Journal, 2024)
Excessive rice consumption with a high glycemic index has a negative effect on health. This study aimed to determine the effects of physical and enzymatic modifications of rice starch on estimated glycemic index (eIG). This study was conducted between June and November 2023. This experimental study used a completely randomized design (CRD) with four treatments: heat moisture treatment (HMT)-microwave, HMT-autoclave, and enzymatic pullulanase (20 units/g rice starch). The observed parameters included the eIG, amylose content, solubility, swelling power, and thermal characteristics. The eIG values  were measured using the in vitro method with four replicates for each treatment. The research data are expressed as the average value ± standard deviation and were analyzed using descriptive methods. The results showed that the HMT-microwave, HMT-autoclave, and enzymatic pullulanase treatments reduced the eIG value of rice starch by 3,06%, 7,19%, and 9,06%, respectively. Thermal analysis using DSC showed that modified starch experienced an increase in the onset temperature (To), peak temperature (Tp), and end-set temperature (Te) compared to normal rice flour. In conclusion, the physical modification of HMT and enzymatic activity can reduce the eIG value of rice starch. This study provides an alternative for the development of functional rice starch-based products with a low glycemic index.